2022
DOI: 10.1075/jlac.00075.pat
|View full text |Cite
|
Sign up to set email alerts
|

Dualisms in Jihad

Abstract: This paper explores how metaphors are employed in jihadist magazines to promote a dichotomist worldview of ‘us’ versus ‘them’, ‘good’ versus ‘bad’, ‘east’ versus ‘west’ and ‘right’ versus ‘wrong’. It argues that juxtapositions in both language and thought help writers to reaffirm and/or challenge certain paradigms. The approach uses critical metaphor analysis (Charteris-Black 2004) to investigate qualitative evidence of conceptual metaphors, focusing on the domains life is a seed, conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Qualitative studies have found that different forms of jihadist discourse include features like merging group and individual identities (Rothenberger et al, 2016); tailoring content to the addressees' perceived gender, as well as perpetuating a differentiation of the social roles of each gender (Johnston, Iqbal & True, 2020; see also Bermingham et al, 2009 on gender differences in radicalized individuals online); a polarized worldview in which agents are ascribed to opposing parties, such as 'good ' or 'bad', 'us' or 'them' (El-Nashar & Nayef, 2019;Etaywe & Zappavigna, 2021;Patterson, 2022); elements that convey negative polarity and explicit judgment in relation to the authors' religious and moral standards (Etaywe & Zappavigna, 2021); legitimizing violence by drawing on moral principles (i.e., a particular understanding of the Islamic religion; Rothenberger et al, 2016;El-Nashar & Nayef, 2019;Etaywe & Zappavigna, 2021); and presenting the Muslim community as a victim of the 'West' (cf. Lorenzo-Dus & Macdonald, 2018;Lorenzo-Dus, Kinzel & Walker, 2018), as a key element of a narrative that may lead radicalized individuals to take on the role of 'righter of wrongs' (Renaut, 2019;cf.…”
Section: Linguistics and Terrorist Discoursementioning
confidence: 99%
“…Qualitative studies have found that different forms of jihadist discourse include features like merging group and individual identities (Rothenberger et al, 2016); tailoring content to the addressees' perceived gender, as well as perpetuating a differentiation of the social roles of each gender (Johnston, Iqbal & True, 2020; see also Bermingham et al, 2009 on gender differences in radicalized individuals online); a polarized worldview in which agents are ascribed to opposing parties, such as 'good ' or 'bad', 'us' or 'them' (El-Nashar & Nayef, 2019;Etaywe & Zappavigna, 2021;Patterson, 2022); elements that convey negative polarity and explicit judgment in relation to the authors' religious and moral standards (Etaywe & Zappavigna, 2021); legitimizing violence by drawing on moral principles (i.e., a particular understanding of the Islamic religion; Rothenberger et al, 2016;El-Nashar & Nayef, 2019;Etaywe & Zappavigna, 2021); and presenting the Muslim community as a victim of the 'West' (cf. Lorenzo-Dus & Macdonald, 2018;Lorenzo-Dus, Kinzel & Walker, 2018), as a key element of a narrative that may lead radicalized individuals to take on the role of 'righter of wrongs' (Renaut, 2019;cf.…”
Section: Linguistics and Terrorist Discoursementioning
confidence: 99%